Atmospheric processes on ice nanoparticles in molecular beams - Fárník, Michal; Poterya, Viktoriya (Frontiers in Chemistry, 2014)
This review summarizes some recent experiments with ice nanoparticles (large water clusters) in molecular beams and outlines their atmospheric relevance: (1) Investigation of mixed water–nitric acid particles by means of the electron ionization and sodium doping combined with photoionization revealed the prominent role of HNO3 molecule as the condensation nuclei. (2) The uptake of atmospheric molecules by water ice nanoparticles has been studied, and the pickup cross sections for some molecules exceed significantly the geometrical sizes of the ice nanoparticles. (3) Photodissociation of hydrogen halides on water ice particles has been shown to proceed via excitation of acidically dissociated ion pair and subsequent biradical generation and H3O dissociation. The photodissociation of CF2Cl2 molecule in clusters is also mentioned. Possible atmospheric consequences of all these results are briefly discussed.